Digital Artefacts and The Role of Digital Affordance. (May 2022) - Colombo, S.; Montagna, F.; Cascini, G.; Palazzolo, V. F.
Abstract: This work investigates how the concept of affordance should be revised following the digital evolution. Starting from a review of the literature about affordance, the most acknowledged constructs are compared with the variegated definitions of digital artefacts. The paper proposes a definition of digital affordance, overcoming the inconsistencies identified in the literature. The study is enriched by a series of interviews to investigate the final users' perception of affordance. Finally, the paper shows the application of the proposed model with a case study related to food delivery services.